2009
DOI: 10.1371/journal.pgen.1000646
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and Specific Roles of the ARGONAUTE Proteins AGO1 and ZLL in Development and Small RNA-Directed Gene Silencing

Abstract: The Arabidopsis ARGONAUTE1 (AGO1) and ZWILLE/PINHEAD/AGO10 (ZLL) proteins act in the miRNA and siRNA pathways and are essential for multiple processes in development. Here, we analyze what determines common and specific function of both proteins. Analysis of ago1 mutants with partially compromised AGO1 activity revealed that loss of ZLL function re-establishes both siRNA and miRNA pathways for a subset of AGO1 target genes. Loss of ZLL function in ago1 mutants led to increased AGO1 protein levels, whereas AGO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 34 publications
5
103
1
1
Order By: Relevance
“…A recent study showed that AGO10 quenches the activity of miR165/166 that moves into AGO10-expressing zone, thus releasing the expression of HD-ZIP III family genes to regulate meristem development (Zhou et al, 2015). In addition to sequestering miR165/166, AGO10 may regulate meristem development through mediating the translational inhibition of multiple miRNA target genes (Brodersen et al, 2008;Mallory et al, 2009) and act partly through miR172 to promote floral determinacy (Ji et al, 2011). AGO10 can also bind vsiRNAs and cooperate with AGO1 to have modest antiviral effect in inflorescences (Garcia-Ruiz et al, 2015).…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
“…A recent study showed that AGO10 quenches the activity of miR165/166 that moves into AGO10-expressing zone, thus releasing the expression of HD-ZIP III family genes to regulate meristem development (Zhou et al, 2015). In addition to sequestering miR165/166, AGO10 may regulate meristem development through mediating the translational inhibition of multiple miRNA target genes (Brodersen et al, 2008;Mallory et al, 2009) and act partly through miR172 to promote floral determinacy (Ji et al, 2011). AGO10 can also bind vsiRNAs and cooperate with AGO1 to have modest antiviral effect in inflorescences (Garcia-Ruiz et al, 2015).…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
“…This revealed that an ago10 mutation partially restores leaf development as well as siRNA and miRNA pathways of ago1-27. 17 Indeed, in the ago1-27 ago10-3 double mutant, miR398 levels were elevated compared to single ago1-27 mutant (although not restored to the WT level), and consequently, both CSD2 mRNAs and protein levels were reduced ( Fig. 2 and see ref. 17 for miR398 and CSD2 mRNA levels).…”
Section: Mutations In Ago Genes Affect the Regulation Of Ccs1 Mrna Bymentioning
confidence: 92%
“…17 Since the combination of null ago1 alleles with ago10 alleles are embryo lethal in both Col and Ler, the hypomorphic Col ago1-27 mutant (with an AGO1 function partially compromised) was combined with ago10-1 or ago10-3 Col mutants. This revealed that an ago10 mutation partially restores leaf development as well as siRNA and miRNA pathways of ago1-27.…”
Section: Mutations In Ago Genes Affect the Regulation Of Ccs1 Mrna Bymentioning
confidence: 99%
“…The expression of AGO10 partially overlaps the expressional domain of AGO1. Fusion of the AGO10 promoter and coding sequence to a reporter gene showed that its expression is more restricted in whole embryos than observed for AGO1, becoming limited to provascular strands and the adaxial side of cotyledons at the globular stage (Mallory et al, 2009). Moreover, the expression of the AGO10 coding sequence, fused to the AGO1 promoter, revealed that this family member can partially compensate for AGO1 activity, to again suggest that AGO10 may be involved in sRNAmediated gene expression regulation in specific cells and/or tissues.…”
Section: Ago10mentioning
confidence: 93%
“…In Arabidopsis, the complete annotation of its genome identified nine other AGO family members (termed AGO2 to AGO10 respectively), and phylogenetic analysis of this protein family at the amino acid level identified three distinct clades, namely the AGO1/AGO5/AGO10, AGO2/AGO3/AGO7, and AGO4/AGO6/AGO8/AGO9 clades (Vaucheret, 2008;Fig.2). It is important to note that although the distribution of the 10 Arabidopsis AGO proteins into three distinct clades is purely based on amino acid sequence homology, and does not directly infer similarities in activity or redundancies in function, several examples of functional redundancy have been identified between AGO clade members, namely between AGO1 and AGO10 of the AGO1/5/10 clade (Mallory et al, 2009), and AGO4, AGO6 and AGO9 of the AGO4/6/8/9 clade (Havecker et al, 2010). In addition to the identification of functional redundancy amongst family members, some Arabidopsis AGO proteins have also been shown to exhibit strong preferences to load sRNA species of a particular size and/or 5' terminal nucleotide (Havecker et al, 2010;Mi et al, 2008;Takeda et al, 2008).…”
Section: The Arabidopsis Argonaute Protein Familymentioning
confidence: 99%